1993
DOI: 10.1016/0014-5793(93)80624-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cAMP dependent CFTR‐chloride channels in human trache gland cells

Abstract: Human tracheal gland cells are believed to be a major site at the origin of cystic fibrosis. Since this disease is due to mutations in a protein called CFTR, we looked for the activity of CFTR in human tracheal gland cells in culture. We have identified CFTR‐like chloride‐selective channels as having a linear current‐voltage relationship and unitary conductance of 7 pS in these cells. In cell‐attached patches, theophylline (1 mM), IBMX (1 mM), or a cocktail of dibutyryl cAMP (1 mM) and IBMX (0.1 mM) promoted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
18
1
2

Year Published

1995
1995
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 35 publications
3
18
1
2
Order By: Relevance
“…However, ion and fluid secretion is reduced in cultures of CF gland cells (18,19) and in glands pharmacologically treated with CFTR inhibitors (20). This is consistent with patch clamp studies of primary cultures of serous cells (21) and the Calu-3 serous cell model (22), which indicate that CFTR is the only physiologically relevant apical anion channel in such cells. Ussing chamber studies with permeabilized cell sheets of Calu-3 cells confirm those studies and further indicate that functional CFTR is required for secretion to calcium-elevating agonists (23,24).…”
supporting
confidence: 72%
“…However, ion and fluid secretion is reduced in cultures of CF gland cells (18,19) and in glands pharmacologically treated with CFTR inhibitors (20). This is consistent with patch clamp studies of primary cultures of serous cells (21) and the Calu-3 serous cell model (22), which indicate that CFTR is the only physiologically relevant apical anion channel in such cells. Ussing chamber studies with permeabilized cell sheets of Calu-3 cells confirm those studies and further indicate that functional CFTR is required for secretion to calcium-elevating agonists (23,24).…”
supporting
confidence: 72%
“…Some of the results were surprising. In the absence of HCO 3 CFTR-dependent mechanism is at work here in the absence of bath HCO 3 Ϫ or CO 2 ? Song et al (23a) also showed that if the droplets initially had a high pH, the surface airway acidified them, and this process was unaffected by CFTR inhibitors or by amiloride.…”
mentioning
confidence: 99%
“…In the model by Devor et al (6), forskolin stimulates Calu-3 cells to secrete but does not activate Na ϩ -K ϩ -2Cl, the main transport pathway by which Cl Ϫ is moved into the cell across the basolateral membrane, leaving HCO 3 Ϫ as the major anion mediating fluid secretion; this model was supported by direct measures of Calu-3 fluid secreted in response to forskolin or VIP, which had average pH Ͼ8 and calculated HCO 3 Ϫ concentrations of 70 -90 mM (11,17). In addition, there is good evidence that CF surface epithelia, at least in culture, produce a fluid that is more acidic than normal (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A decreased CI-permeability [9] and a constitutive hypersecretion [10] have been reported in cultured CF tracheobronchial gland cells. Furthermore, a high expression of CFTR mRNA and protein [11][12][13] and of CFTR-Iike C1 channels [14] were demonstrated in normal human tracheobronchial glands. We recently showed [12] that CFTR was specifically associated with the membrane of serous cell secretory granules.…”
Section: Introductionmentioning
confidence: 99%